WORK SCENARIOS FOR THE DESIGN OF A DISTILLERY FOR ORGANIC SPIRITS PRODUCTION - Sosa Gómez, Eliani; Gallardo Aguilar, Irenia; Pérez Mojica, Jefferson; de Armas Martínez, Ana Celia (Centro Azúcar Journal, 2025)
Introduction: Currently, organic products have a great demand in the market and have a higher price, which makes them an excellent business opportunity. Objective: To compare two work scenarios for the design of a small distillery to obtain organic spirits. Materials and Methods: The fundamental raw material is organic molasses, obtained from sugar cane grown only with natural fertilizers, using juice from filters during the harvest period, and organic honey and water after the harvest, taking into account the availability of said raw materials by applying mass and energy balances. Results and Discussion: The use of filter juice provides 40% of the ART, which is needed for the beating in fermentation providing a saving in molasses that allows the extension of work outside the harvest period to 26 days in the first scenario and 45 days in the second scenario. This also translates into water savings when working during the harvest period. The project proved to be profitable for a sale price of organic spirit between 190 - 225 $/hL. Conclusions: The addition of juice from the filters significantly reduced the demand for molasses and water, extending the work days outside the harvest. The production of organic spirit in Cuba is presented as a viable and profitable alternative as long as the necessary raw material is available for the scheduled work days.